The Response of the Pulp-Dentine Complex, PDL, and Bone to Three Calcium Silicate-Based Cements: A Histological Study in an Animal Rat Model - Ranjdar Mahmood Talabani; Balkees Taha Garib; Reza Masaeli (Bioinorganic Chemistry and Applications)
Objective. The aim of this study was to histologically examine the tissue reaction of three different calcium silicate cements in the closure of perforations in rat incisor teeth. Material and Methods. An experimental lateral root perforation with pulp exposure was performed in 32 lower incisors of 16 male Wistar albino rats. They were randomly assigned into three test groups (each including eight teeth) that were filled either by Biodentine (BD) or MicroMega mineral trioxide aggregate (MM-MTA) or EndoSequence root repair material putty (ESRRM putty), besides eight unperforated incisors from the other four rats (control group). The inflammatory response and healing process were evaluated histologically and scored after one and four weeks. Differences among groups were tested by Kruskal–Wallis tests at P≤0.05. Results. In the first week, BD produced more inflammatory response in the pulpal (score 3) than other materials (score 2). Only ESRRM putty showed odontoblast-like cells in 50%, 25% dentine-like deposit, 25% evidence of bone deposition in the drilling site (score 2), and minimum periodontal ligament (PDL) necrosis and disorganization (25%, score 2). After one month, all groups had healthy pulpal tissue, but 25% of ESRRM putty retained score 1 inflammatory response, and 50% of the BD case had an incomplete palisading odontoblast layer (score 3). A thick and regular dentine bridge deposition was seen in the ESRRM putty group in comparison with MM-MTA and BD cases. The cortical plate healing in all ESRRM putty samples was complete (score 3), while an incomplete closure was seen in MM-MTA and BD groups (score 2). Both the MM-MTA and ESRRM putty groups had fully organized PDL (score 2), while in 50% of BD cases, a necrotizing area and disorganized PDL with inflammatory cells infiltration were still present. Statistically significant differences in the scores of any histologic parameters among the three tested materials were observed neither in the 1st nor in the 4th weeks of the experimental period. Conclusion. Better tissue compatibility and repair of pulpal and periodontal tissue have been detected after lateral perforation in the root of rat incisors when treated with ESRRM putty than MM-MTA and BD. However, the difference was not significant.